Is Meaningful Work a Stronger Predictor of Innovation Than Transformational Leadership? - MacLachlan Sedger, Andrew Kenneth; Konrad Wiener, Karl Kilian (World Journal of Business and Management, 2024)
Purpose: Innovation is recognised as a key driver of business and economic growth. However, many organisations struggle to implement or encourage innovation successfully. A number of factors, including the demonstration of transformational leadership, have been examined in encouraging innovation behaviour among employees. ‘Meaningful work’ is seen as an additional factor influencing innovation but has received little attention in this field. Design: Drawing on both an emerging body of research on meaningful work and a leading model of creativity and innovation in organisations, this exploratory study of 100 Australian adult employees investigated the additional predictive value of both meaningful work and transformational leadership on innovation behavior. Findings: Results showed that meaningful work was positively correlated with, and predicted, innovation, while transformational leadership did not contribute to innovative behaviour. Implications: This finding has implications for organisations fostering innovation by helping them better understand the impact meaningful work could have on their innovation objectives. Originality: This is one of the first studies examining the relationship between innovation, meaningful work, and transformational leadership in a population of employed adults.